Focused Group Interview in Education Research - Gierszewski, Dorota (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
The focus group interview method provides a research instrument for collectingqualitative data by analysing the opinions, views and perceptions of participants in an interactivesituation supported by an appropriate infrastructure. The article presents the potentialof using focus groups in andragogy research, highlighting their growing popularity. Thetext presents the focus group interview method, taking into account the different variantsand the methodology of application. Both the potential and limitations of using this methodare discussed, particularly in the context of qualitative research focused on the process ofadult learning.